2013
DOI: 10.3168/jds.2013-6752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weekly regrouping of prepartum dairy cows on innate immune response and antibody concentration

Abstract: Objectives were to evaluate the effects of a stable prepartum grouping strategy on innate immune parameters, antibody concentration, and cortisol and haptoglobin concentrations of Jersey cows. Cows (253±3 d of gestation) were paired by gestation length and assigned randomly to the stable (all-in-all-out; AIAO) or traditional (TRD) treatment. In the AIAO treatment, groups of 44 cows were moved into a pen where they remained for 5 wk, whereas in the TRD treatment, approximately 10 cows were moved into a pen week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…There were no differences between treatments in plasma concentrations of NEFA or BHB, the incidence of retained placenta, metritis, endometritis, lameness or early culling, the prevalence of persistent anovulation, pregnancy at first or second insemination or energy-corrected milk yield. In a subset of 34 to 40 cows per treatment, there were no differences between treatments in neutrophil phagocytosis or oxidative burst function or expression of L-selection or CD18, production of IgG against ovalbumin, serum haptoglobin concentrations or concentrations of cortisol in blood (Silva et al, 2013a).…”
Section: Management and Social Stress Effectsmentioning
confidence: 87%
“…There were no differences between treatments in plasma concentrations of NEFA or BHB, the incidence of retained placenta, metritis, endometritis, lameness or early culling, the prevalence of persistent anovulation, pregnancy at first or second insemination or energy-corrected milk yield. In a subset of 34 to 40 cows per treatment, there were no differences between treatments in neutrophil phagocytosis or oxidative burst function or expression of L-selection or CD18, production of IgG against ovalbumin, serum haptoglobin concentrations or concentrations of cortisol in blood (Silva et al, 2013a).…”
Section: Management and Social Stress Effectsmentioning
confidence: 87%
“…Very little peer-reviewed literature has examined metabolic health of transition cows relative to housing environment. Two recent studies with adequate statistical power that examined prepartum housing found no difference in the incidence of retained fetal membranes or metritis or in concentrations of NEFA or BHB with housing strategies intended to reduce social stress (Silva et al 2013a(Silva et al , 2014.…”
Section: Discussionmentioning
confidence: 98%
“…This important result can be explained on the basis of many aspects. Animals in group housing are often regrouped with unfamiliar herd-mates [34,45,46], and this regrouping can induce stress-related behavioural and physiological reactions. Generally, after relocating into the unknown barn, cows stand only, do not want to eat and lie down, and relax.…”
Section: Discussionmentioning
confidence: 99%